Geodesic connectedness of a spacetime with a causal Killing vector field. - Bartolo, Rossella (My University, 2024)
We study the geodesic connectedness of a globally hyperbolic spacetime (M, g) admitting a complete smooth Cauchy hypersurface S and endowed with a complete causal Killing vector field K. The main assumptions are that the kernel distribution D of the one-form induced by K on S is non-integrable and that the gradient of g(K, K) is orthogonal to D. We approximate the metric g by metrics gε smoothly depending on a real parameter ε and admitting K as a timelike Killing vector field. A known existence result for geodesics of such type of metrics provides a sequence of approximating solutions, joining two given points, of the geodesic equations of (M, g) and whose Lorentzian energy turns out to be bounded thanks to an argument involving trajectories of some affine control systems related with D.
Keywords: Riemann, Geometría de; Globally hyperbolic spacetime; Causal Killing vector field